Girls (and Boys) and Technology (and Toys) - Upitis, Rena (Canadian Journal of Education/Revue canadienne de l’éducation, 2001)
In this inquiry, I have examined how 11- to 14-year-old students used technology to design and produce toys. While most students created toys by hand, I explored the range of computer use, and male and female students’ views of this integrated unit. In addressing three specific research questions, I found that a project-based unit allowed students to use technology in meaningful ways, that the wide variety of computer use disrupted typical gender-technology patterns, and that computer use allowed some shifts in traditional gender-technology relations. L’étude porte sur les diverses utilisations de l’ordinateur et sur la manière dont les garçons et les filles de 11 à 14 ans perçoivent l’unité intégrée qu’est un jouet conçu par ordinateur. Les résultats suggèrent qu’une unité axée sur un projet permet aux élèves de se servir de la technologie de manière intéressante, que la variété des utilisations de l’ordinateur modifie profondément les modèles typiques quant à la technologie et aux différences entre les sexes et que l’utilisation de l’ordinateur permet certains changements dans les rapports traditionnels entre la technologie et les sexes.